2003
DOI: 10.1111/j.1755-618x.2003.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Politicizing Aboriginal Cultural Tourism: The Discourse of Primitivism in the Tourist Encounter*

Abstract: Le tourisme cultural amérindien est un secteur de L'industrie touristique canadienne potentiellement en forte croissance, qui connaît un vif succès auprès des visiteurs européens, surtout les Allemands. Le présent article recourt à L'analyse du discours pour examiner les rencontres touristiques qui se déroulent dans les différents lieux touristiques amérindiens du sud de L'Alberta. Il analyse la construction de L'«indianite» et de la culture amérindienne par les guides amérindiens et les visiteurs étrangers. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Tour leaders ensure that commercial transactions with Thais occur beyond the immediate gaze of adventurers who, buoyed by the sense that they are participating in genuine cultural interactions with locals, are convinced that their overnight homestays stem principally from an intrinsic Thai hospitality and generosity rather than from the financial rationale often driving these, and other, encounters between adventurers and Thais. (Kontogeorgopoulos, 2003, p. 188) Similarly, Deutschlander and Miller (2003) found that in Indigenous tourist sites in southern Alberta, Canada, Indigenous peoples were active collaborators in the suppression of commodification, emphasizing instead the spiritual aspects of the cultural experience. Interactions with local peoples in contexts of mundane, everyday life, devoid of monetary transactions, are precisely the practices that are absent in enclavic tourist sites (Edensor, 1998) and that define off-the-beaten-track travel as an idealized form.…”
Section: Non-commodification As a Signifier Of Intimacymentioning
confidence: 93%
See 1 more Smart Citation
“…Tour leaders ensure that commercial transactions with Thais occur beyond the immediate gaze of adventurers who, buoyed by the sense that they are participating in genuine cultural interactions with locals, are convinced that their overnight homestays stem principally from an intrinsic Thai hospitality and generosity rather than from the financial rationale often driving these, and other, encounters between adventurers and Thais. (Kontogeorgopoulos, 2003, p. 188) Similarly, Deutschlander and Miller (2003) found that in Indigenous tourist sites in southern Alberta, Canada, Indigenous peoples were active collaborators in the suppression of commodification, emphasizing instead the spiritual aspects of the cultural experience. Interactions with local peoples in contexts of mundane, everyday life, devoid of monetary transactions, are precisely the practices that are absent in enclavic tourist sites (Edensor, 1998) and that define off-the-beaten-track travel as an idealized form.…”
Section: Non-commodification As a Signifier Of Intimacymentioning
confidence: 93%
“…(1998, p. 79) In their article on the political possibilities of Indigenous tourist sites in southern Alberta, Deutschlander, and Miller (2003) found that the legacies of colonialism were clearly articulated by Indigenous guides and in museum displays. In such cultural spaces, as a contrast to designated political spaces, these critical political perspectives were relatively openly received by non-Indigenous people.…”
Section: Beyond Orientalism?mentioning
confidence: 97%
“…Despite the challenges and problems associated with tourism activity, governments, the tourism industry and indigenous communities and individuals continue to actively pursue tourism as a development tool to provide a better socioeconomic future (Altman 1996;Butler and Hinch 2007;Deutschlander and Miller 2003;Fuller et al 2005;Ryan 2002). And, even though indigenous tourism in Australia is considered a niche sector of Australia's tourism industry (Hollinshead 1996;Tourism Research Australia 2011;Whitford and Ruhanen 2010), it does contribute to the overall growth and development of tourism in the country.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Tourism is undoubtedly a significant economic, sociocultural and political phenomenon and has increasingly been identified as a means for indigenous peoples and communities to develop, among other things, a better socioeconomic future (Butler and Hinch 2007;Deutschlander and Miller 2003;Ryan and Huyton 2002;Fuller et al 2005). For instance, indigenous tourism can be leveraged as a socio-economic opportunity for indigenous peoples, providing a pathway to greater economic and social development, greater independence, increased employment opportunities and reduced reliance on government transfers (Butler and Hinch 2007;Gale 2013: Dyer et al 2003;Higgins-Desbiolles et al 2010;Rivers 2012;Russell-Mundine 2007;Whitford and Ruhanen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A contemporary goal of interpretation is to create a bridge between traditional indigenous cultures and modern audiences (Batten 2005). The hope is to provide those cultures with a stronger voice (Deutschlander and Miller 2003;Strange and Kempa 2003;Krmpotich and Anderson 2005). Successful interpretive techniques for relating to the audience include generating emotional arousal and connecting with visitors' previous experiences and knowledge using innovative techniques (Uzzell and Ballantyne 1998;Gross and Zimmerman 2002;Ballantyne 2003;Knapp and Benton 2004).…”
Section: Reviewing the Meaning-making Literaturementioning
confidence: 99%